Hubungan Religiusitas dengan Prestasi Belajar pada Siswa Putri di SMK Telkom Shandy Putra Medan - Kombih, Ismail (JURNAL SOCIAL LIBRARY, 2021)
Referring to the target to be achieved, this study uses quantitative research methods. This study uses a correlational quantitative method, which aims to see the relationship between the independent variables and the dependent variable. The population in this study were all 11th grade students of SMK Telkom Shandy Putra Medan who participated in religious organizations. Consists of 50 students. The sample in this study amounted to 50 students. The sampling technique used for this research is total sampling. The results of the normality test showed thescore Kolmogorov-Smirnovof the learning achievement variable was 0.717 with p= 0.689 (p> 0.05), which means that the learning achievement variable had data that were normally distributed. The religiosity variable also has a normal data distribution with ascore Kolmogorov-Smirnov of 0.744 with p= 0.637 (p> 0.05), which means that this variable has normally distributed data. Complete results from the normality test of research data can be seen in the appendix. The linearity test of the relationship between the religiosity variable and learning achievement resulted in F = 29.226 with a significance value of p= 0.000 (p